Research Advances on Anti-Cancer Natural Products - Guo, Meng; Jin, Jie; Zhao, Dong; Rong, Zheng; Cao, Lu-Qi; Li, Ai-Hong; Sun, Xiao-Ying; Jia, Li-Yi; Wang, Yin-Di; Huang, Ling; Li, Yi-Heng; He, Zhong-Jing; et al. (Frontiers in Oncology, 2022)
Malignant tumors seriously threaten people’s health and life worldwide. Natural products, with definite pharmacological effects and known chemical structures, present dual advantages of Chinese herbs and chemotherapeutic drug. Some of them exhibit favorable anti-cancer activity. Natural products were categorized into eight classes according to their chemical structures, including alkaloids, terpenoids and volatile oils, inorganic salts, phenylpropanoids, flavonoids and isoflavones, quinone, saponins and polysaccharides. The review focused on the latest advances in anti-cancer activity of representative natural products for every class. Additionally, anti-cancer molecular mechanism and derivatization of natural products were summarized in detail, which would provide new core structures and new insights for anti-cancer new drug development.